Prostate cancer with metastasis to the omentum and massive ascites: A rare manifestation of a common disease - Zagouri, F.; Papaefthimiou, M.; Chalazonitis, A.N.; Antoniou, N.; Dimopoulos, M.-A.; Bamias, A. (Onkologie, 2009)
Background: The most common sites of metastasis in prostate cancer include bone and regional lymph nodes followed by lung, liver, and brain. Peritoneal metastasis without skeletal involvement is extremely rare. Case Report: We present herein a patient with hormone refractory prostate cancer with peritoneal metastasis accompanied by ascites but without bone metastasis. The patient initially experienced an excellent response to docetaxelbased chemotherapy. Conclusions: Prostate cancer can present with distant metastasis in unexpected sites. The lack of skeletal involvement does not exclude the possibility of distant metastases. The presence of ascites may indicate peritoneal disease which could be responsive to current standard chemotherapy. Copyright © 2009 S. Karger AG.
Keywords: Ascites; Docetaxel; Metastasis; Omentum; Prostate cancer; relapse